Strategies for Upgrading MSMEs Through the Optimization of KUR Financing Utilization at Bank Syariah Indonesia in the Bogor Area - Anum Syantining Sari; Hartrisari Hardjomidjojo; Sapta Raharja (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
One of the fundamental problems faced by MSMEs is limited capital. Although MSMEs may have received financing, many still encounter obstacles in elevating their business category. Among these factors are financial literacy and financial inclusion. Therefore, in this study, the data were collected through questionnaires and interviews with 113 MSMEs that have received KUR financing from BSI in the Bogor Area, using purposive sampling. The analytical methods used in this study include both qualitative and quantitative descriptive analysis. This includes classical assumption tests, regression model estimation, and hypothesis testing (t-test). Strategy development uses the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices, SWOT analysis and QSPM. The QSPM analysis identifies three top-priority strategies that most significantly support MSMEs in upgrading their business class after receiving KUR financing from BSI in the Bogor Area: (1) enhancing financial inclusion by providing easier access to banking services, both savings and financing. (2) improving the reputation and role of KUR in assisting unbankable MSMEs to become bankable and move up in business class. (3) increasing financial literacy among customers to encourage the use of BSI bank accounts for transactions, including digital transactions.